Representasi Simbolik Rejang Inyeng Melalui Film Dokumenter di Desa Adat Tiyingan Kabupaten Badung: Indonesia - Sukadana, I Putu; Suyoga, I Putu Gede; Dinata, Ramanda Dimas Surya; Hendrawan, Freddy (Besaung : Jurnal Seni Desain dan Budaya, 2025)
Rejang Inyeng  is a sacred dance preserved in Tiyingan Village, Petang District, Badung Regency. Performed by young girls before menstruation during the Purnama Kapat and Purnama Kedasa ceremonies, the dance functions as a ritual to welcome deities. However, its continuity faces challenges due to limited academic documentation and a hiatus during the pandemic. This study aims to represent the symbolic meaning of Rejang Inyeng  through documentary film as a cultural preservation strategy. The research employed a qualitative approach by combining Ferdinand de Saussure’s semiotics, visual ethnography, and the Save the Cat narrative model. Data were collected through observation, interviews, questionnaires, literature studies, and documentation, while information tracing was guided by the concept of Catur Guru and the Glass Box method. Analysis was conducted by linking signifiers, such as dance movements and performers, with signifieds such as purity, sanctity, and cultural regeneration, further deepened through the concept of Dasa Aksara. The findings indicate that the documentary effectively represents the symbolism of Rejang Inyeng  in a communicative way, serving not only as a visual archive but also as an educational and cultural transmission medium. The novelty of this research lies in the integration of Saussurean semiotics with Dasa Aksara, the application of Catur Guru in data exploration, and the adaptation of Save the Cat within a sacred documentary.